The Recontruction Of Chemistry Curriculum Elements Of Vocational School For Nursing Skills Study Programs - Anisa Wiranda; Momo Rosbiono; Sjaeful Anwar (Journal of Educational Sciences, 2021)
Chemical teaching materials don’t support the learning of nursing vocational competencies, so it is necessary to analyze the suitability of chemical content with nursing vocational content. This research aims to reconstruct elements of the chemical curriculum relevant to the competence of nursing vocational schools. The research design used is Developmental Research with the stages of design, development, and evaluation. The research was conducted at SMK Nusa Bhakti Bandung and SMKN 1 Koto Besar (Dharmasraya Regency). The study involved two chemistry education experts, six nursing vocational teachers, and six chemistry teachers in nursing. The research instruments used are formulation formats in the form of KD, chemical content, knowledge dimensions, learning strategies, and learning evaluations that have been validated. The data of the research results was analyzed in a qualitative descriptive way then used as input for product improvement. The results showed that design of KD, chemical content, knowledge dimensions, learning strategies, and learning evaluation developed have good relevance to the demands of nursing vocational competencies. Viewed from the validation of teachers in nursing vocational schools obtained good validation results.